Designing subsea coaxial channel model as FIR filter on MATLAB - Kanisin, Devaraj; Tang, Sai Hong; Ismail, Napsiah (Federation of Engineering Institutions of Islamic Countries, 2006)
The paper presents the design of subsea coaxial channel model as a FIR filter on MATLAB. The subsea coaxial cables are commonly used in telecommunication industry and, oil and gas industry. Furthermore, this cable is unlike a filter circuit, which is a “lumped network” as individual components appear as discrete items. Therefore, a subsea coaxial network can be represented as a digital filter. In overall, the study has been conducted using MATLAB to design the subsea coaxial channel model base on primary and secondary parameters of subsea coaxial cable.